2014
DOI: 10.1089/ten.tec.2013.0298
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic Membrane Scaffolds Enable the Development of Tissue-Engineered Urothelium with Molecular and Ultrastructural Properties Comparable to that of Native Urothelium

Abstract: The amniotic membrane (AM) is a naturally derived biomaterial that possesses biological and mechanical properties of great importance for tissue engineering. The aim of our study was to determine whether the AM enables the formation of a normal urinary bladder epithelium-urothelium-and to reveal any differences in the urothelial cell (UC) growth and differentiation when using different AM scaffolds. Cryopreserved human AM was used as a scaffold in three different ways. Normal porcine UCs were seeded on the AM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 39 publications
(39 reference statements)
1
47
1
1
Order By: Relevance
“…Studies of the AM in urology have shown it to be a suitable scaffold that promotes urothelial cell proliferation and differentiation, which may enable the development of tissue-engineered urotheliums with molecular and ultrastructural properties comparable to that of native tissues. [70] The AM and amniotic fluid have also been used in gastroenterological surgery to prevent peritoneal adhesions. [71] Further clincial applications include treatments for congenital absence of the vagina, replacing nasal mucosa, bladder wall reconstruction, as well as microvascular interpositional grafting.…”
Section: Placental-derived Biomaterials By Medical Specialtymentioning
confidence: 99%
“…Studies of the AM in urology have shown it to be a suitable scaffold that promotes urothelial cell proliferation and differentiation, which may enable the development of tissue-engineered urotheliums with molecular and ultrastructural properties comparable to that of native tissues. [70] The AM and amniotic fluid have also been used in gastroenterological surgery to prevent peritoneal adhesions. [71] Further clincial applications include treatments for congenital absence of the vagina, replacing nasal mucosa, bladder wall reconstruction, as well as microvascular interpositional grafting.…”
Section: Placental-derived Biomaterials By Medical Specialtymentioning
confidence: 99%
“…These assays typically utilize primary, immortalized, or cancer cell lines derived from the bladder urothelium or from the kidneys (e.g., proximal tubule epithelial cells). Host bladder cells are usually grown as undifferentiated monolayers but can be induced to stratify and partially differentiate when grown with appropriate media on membrane scaffolds in dishes or under microgravity conditions generated within rotary walled vessel bioreactors (153)(154)(155). Recently, culture systems that incorporate different types of host cells, such as neutrophils plus bladder epithelial cells, have been established to better approximate the cellular complexity of the inflamed urothelium (156).…”
Section: Cell Culturementioning
confidence: 99%
“…Despite the proven utility of cell culture-based model systems, they cannot fully recapitulate the complexity of the host environment with its myriad cell types, complicated tissue architecture, variable nutrient levels, and teeming host defenses. For example, key features of terminally differentiated superficial umbrella cells, including their multiple nuclei and quasicrystalline arrays of apical uroplakin complexes, are exceptionally difficult to mimic in cell culture, although notable progress in this area has been made with primary urothelial cells in recent years (154,182). Therefore, detailing the molecular consequences of UPEC interactions with bladder umbrella cells is currently limited in the context of cell culture-based models.…”
Section: Cell Culturementioning
confidence: 99%
“…They measure 150-300 μm in length and are up to three times larger than normal-sized superficial UCs (Kreft et al 2005). Superficial UCs are also hexagonally packed, thus having less cell-cell contact per unit area (Claude 1978;Anderson and Van Itallie 2009;Jerman et al 2013). On the other hand, interdigitation of adjacent cells increases the amount of junction per unit area (Claude 1978).…”
Section: The Paracellular Pathwaymentioning
confidence: 99%
“…Fig. 4 Uroplakin and aquaporin (AQP) expression in urothelial constructs on stromal amniotic membrane scaffolds in vitro prepared as described in Jerman et al (2013). Note uroplakins at the apical plasma membrane of superficial urothelial cells (UCs) in urothelial constructs, suggestive of terminal differentiation.…”
Section: The Mucin Layermentioning
confidence: 99%